Deciding on an Objection in the Administrative Procedure: Legal Nature of the Decision - Radošević, Ratko S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
An objection is a "legal remedy" in administrative procedure, used against new forms of "administrative activities": due to non-fulfillment of obligations from the administrative contract, against administrative actions and due to the manner of providing public services. The objection is decided by a decision, which should have the character of an administrative act. In this way, legal protection against new forms of “administrative activities" should be introduced into régime administratif, which includes an appeal in the administrative procedure and a lawsuit in the administrative dispute. This decision, however, reminds of an administrative act only by name – not by its features. Such a conclusion is indicated by the legal definitions of the administrative act, in the General Administrative Procedure Act and the Administrative Disputes Act. In short, this decision is not an administrative act because the situations in which it is made are not administrative matters, but various situations, of different legal nature.
Keywords: administrative procedure, objection, decision, administrative act, administrative matter